Road traffic safety perception in Jordan. Issue 1 (31st December 2016) - Shbeeb, Lina I.; Awad, Wa'el H.
Abstract: In the past 20 years, several safety measures were taken in an attempt to reduce traffic-related fatalities. Although reduction in deaths was occasionally noticed, the sustainability of that trend has never achieved. This study explores Jordan safety profile trying to explain the traffic safety trend. It examines road traffic safety perception of both public community and road specialist. Main turning points that may have contributed in explaining prevailing traffic safety conditions have been collected. A questionnaire is administered to two distinct groups of the Jordanian society (general public and road specialist) with a total of 167 subjects. The subjects were asked to evaluate the effectiveness of a list of safety measures. Results showed that government took effective but not sustainable measures (mainly enforcement and legislative). Other ineffective measures (administrative and engineering) were taken but they were not target oriented. The main focus of interviewed subjects in order to improve traffic safety in Jordan is to establish sustainable engineering measures and improving the vehicle fleet, driver licensing, and testing procedures. As a surprising result, enforcement measures were not considered as desirable as other measures.